1997
DOI: 10.1002/bjs.1800840914
|View full text |Cite
|
Sign up to set email alerts
|

Importance of eliminating portal flow to produce large intrahepatic lesions with interstitial laser coagulation

Abstract: Hepatic blood flow substantially reduces the size of the lesion produced by laser coagulation. Portal flow should therefore be occluded during laser treatment to produce lesions of clinically relevant dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…However, further research in this field is needed to elucidate (a) the exact correlation between histopathologic structure and laser energy and (b) the correlation between hepatic blood flow and the actual extent of the area of necrosis (46). …”
Section: Discussionmentioning
confidence: 99%
“…However, further research in this field is needed to elucidate (a) the exact correlation between histopathologic structure and laser energy and (b) the correlation between hepatic blood flow and the actual extent of the area of necrosis (46). …”
Section: Discussionmentioning
confidence: 99%
“…During local ablation, the Pringle manoeuvre is chosen by the majority of surgeons. Portal clamping, which is applied by 4% of surgeons, may be advantageous in thermal destruction techniques, as it provides an increase in lesion size, but minimizes ischaemic damage [10, 24]. By those who clamp routinely during local ablation, intermittent clamping is favoured, corresponding to ischaemia times of 15–30 min, whereas for the majority of surgeons who clamp on indication, a shorter continuous Pringle manoeuvre seems to be preferable.…”
Section: Discussionmentioning
confidence: 99%
“…For non-resectable liver tumours thermal destruction techniques, such as radiofrequency ablation, laser-induced thermotherapy and microwave therapy, provide local tumour control and improve life expectancy [7,8,9]. During thermal ablation, vascular clamping is advised to reduce dissipation of the generated heat, which creates larger destruction volumes, resulting in greater tumour-free margins [10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…8 -10 During local ablation, vascular clamping is applied to increase destruction volumes. 11,12 However, vascular clamping induces ischemia/reperfusion (I/R) injury to the liver parenchyma and may contribute to postoperative morbidity. [13][14][15] Moreover, we have recently demonstrated that the outgrowth of pre-established micrometastases was strongly stimulated after I/R in a murine model.…”
mentioning
confidence: 99%